ANALISIS SWOT DALAM STRATEGI PENGEMBANGAN USAHA TANAMAN HIAS BONSAI PADA JUN BONSAI KECAMATAN SUKOLILO KOTA SURABAYA - Edo Pratama; Nekky Rahmiyati (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the business development strategy of bonsai ornamental plants at Jun Bonsai in Sukolilo District, Surabaya City, using the SWOT analysis method. This research was conducted to identify internal and external factors that affect business development and formulate appropriate strategies to improve the company's performance and competitiveness. The methods used include Business Model Canvas (BMC) to map the business model, SWOT analysis, IFAS and EFAS Matrix, and economic analysis to determine the Break Even Point (BEP). The results showed that Jun bonsai has dominant strengths compared to weaknesses, the company is in quadrant I which means it has a strong competitive position. strong competitive position. The development strategy that can be used is to focus on utilizing internal strengths and external opportunities (S-O strategy). The results of the analysis show that Jun Bonsai has great potential to grow, but is also faced with various challenges, such as intense competition and lack of customer education regarding bonsai care. This research recommends that Jun Bonsai continue to innovate in products and marketing strategies, This research is expected to contribute to the development of science in the field of entrepreneurship and become a reference for further research.